Evaluation of Diagnostic Accuracy of Gene Xpert MTB/RIF in Patients with Tuberculous Lymphadenitis using Fine Needle Aspirate in a Tertiary Care Hospital - Nadeem, Saima (International Journal of Pathology, 2022)
Tuberculous lymphadenitis form the largest proportion of extrapulmonay manifestation of tuberculosis and it’s diagnosis always remains a challenge. Cytology and microscopy have suboptimal sensitivity and specificity, therefore accurate identification and timely cure of tuberculosis can lessen morbidity and mortality associated with TB lymphadenitis. The aim of this study was to evaluate the sensitivity and specificity of GeneXpert/RIF against smear and gold standard culture.Objectives: The objective of this study was to demonstrate the diagnostic precision of GeneXpert MTB/RIF on fine needle aspiration cytology (FNAC) of cases clinically suspected to have tuberculous lymphadenitis and comparison with smear and culture as a yardstick.Methodology: The present study is a cross sectional type piloted in Khyber Girls Medical College and the samples were collected from all the three tertiary care hospitals of Peshawar from June 2019- June 2020. Those patients who were suspected to have TB lymphadenopathy were included in this study and were subjected to FNAC. The sample was then processed for routine cytology and Ziehl Nelson staining, GeneXpert assay and Lowenstein Jensen culture. Rifampicin resistance was also determined by GeneXpert.Results: A total of 100 cases with adequate aspirate on fine needle aspiration cytology were included in this study. Out of these 50(50%) showed cytological features consistent with mycobacterial infection. The sensitivity of Xpert equated to culture was 94 %( 95% CI 75-97%) while specificity was 70% (95% CI 60-70%). The sensitivity of smear matched to culture was 37% (95 % CI 26-39 %) and specificity was 98% (95% CI 96-100 %). When the results of Xpert were equated with smear the sensitivity as well as specificity was 100% in those cases which were positive on both smear and culture. On the other hand cases which were negative on smear but positive on culture demonstrated sensitivity of 92% and specificity of 100 % when matched with Xpert. The outcome of RIF by Xpert was in total agreement with conventional drug sensitivity tests.Conclusion: GeneXpert MTB/RIF is an excellent and time saving automated technique for confirmation of MTB in lymph node aspirates and at the same time determines rifampicin resistant cases.